Carbodiimide-based synthesis of N-heterocycles: moving from two classical reactive sites to chemical bond breaking/forming reaction - Wang, Yang; Zhang, Wen-Xiong; Xi, Zhenfeng (Chemical Society reviews, 2020)
Carbodiimides are a unique class of heterocumulene compounds that display distinctive chemical properties. The rich chemistry of carbodiimides has drawn increasing attention from chemists in recent years and has made them exceedingly useful compounds in modern organic chemistry, especially in the synthesis of N-heterocycles. This review has outlined the extensive application of carbodiimides in the synthesis of N-heterocycles from the 1980s to today. A wide range of reactions for the synthesis of various types of N-heterocyclic systems (three-, four-, five-, six-, seven-, larger-membered and fused heterocycles) have been developed on the basis of carbodiimides and their derivatives. The extensive synthetic application of carbodiimides in various types of N-heterocyclic systems from the 1980s to today is outlined.